Theoretical Review of The Nature and the Possibilities of Inclusive Catholic Education in Lithuania - Voidogaitė, Viktorija (Journal of Education Culture and Society, 2024)
Aim. The aim of this theoretical review is to identify the possibilities of inclusive education in a Catholic school. The review seeks to describe the ways in which such schools have already chosen to engage or not engage in compulsory inclusive education in Lithuania. It also seeks to highlight the Catholic Church’s teaching on inclusion of vulnerable groups. Methods. Analysis and synthesis of scientific literature. Analysis and synthesis of Catholic Church documents. Results. The analysis and synthesis of the scientific literature revealed that Catholic educational institutions in Lithuania implement one of the following three ways of contact with inclusion: a) full inclusion, b) gradual involvement in the state strategy of inclusion, c) segregation of pupils at the time of admission to the school. The analysis and synthesis of Catholic Church documents has shown that the Church’s teaching on the inclusion of vulnerable groups unequivocally invites, encourages and even insists that schools become open to all children and their needs. Conclusions. The very nature of the Church community is inherently inclusive and has no room for discrimination; on the contrary, its weakest members should be the most lovingly protected. The development of Catholic education is bound up not only with the creators of specific educational paradigms, but also with the changes in general education in a particular context. Although concrete practices are gradually changing and showing good trends towards inclusiveness, some schools retain a strong elitist character and tend to offer aid as a form of charitable action outside the formal schooling.